ISLAMIC EDUCATION LEADERSHIP IN BUILDING TOLERANCE OF RELIGIOUS LIFE IN BALUN VILLAGE, TURI SUB-DISTRICT, LAMONGAN DISTRICT - Solchan Ghozali (Universitas Islam Malang, 2021)
The research objective is to describe, analyze, and interpret the type of Islamic education leadership in building religious tolerance, the role of Islamic education in building tolerance in religious life, Islamic education leadership models in building tolerance of religious life. This study uses a qualitative approach to the type of phenomenology. Data collection was carried out through in-depth interviews, participant observation and documentation study. Determination of informants was carried out using purposive sampling and snowball sampling techniques. The data analysis technique uses the interactive model analysis technique of Miles and Huberman. While the data validity test technique used triangulation technique. The results of the study answered the focus that the type of Islamic education leadership in building religious tolerance is collaborative-paternalistic-democratic. The paternalistic type referred to is the type of leadership that is fatherly, protective, and educational. Meanwhile, the democratic type is meant to treat everyone equally and to provide opportunities for diverse and diverse communities to actively participate in realizing a harmonious and peaceful religious life. This type of leadership is characterized by the following characters of religious leaders: a) Promoting tolerance and togetherness; b)Â Protecting; c) Prioritizing human dignity. The role of the leadership of Islamic education in building tolerance in religious life is as: a) religious experts; b) role models in behavior; c) As well as Mediators. Religious leaders carry out a leadership mechanism in maintaining the socio-cultural system that has survived for decades. Some changes are evolutive. However, for decades, the values of togetherness, harmony and tolerance have been substantively maintained by society. This is inseparable from the leadership role of religious leaders who are united in being committed to maintaining harmony and peace between religious communities. The leadership model of Islamic education is transformational-internal-collective. The transformational leadership model is characterized by several patterns of behavior as follows: a) Implanting trust; b) Civilizing art; c) Maintaining tradition; d) Educating and guiding; and e) Maintaining effective communication. Religious leaders carry out their leadership duties collectively. This means that religious leaders collaborate collegial on it collectively to become joint leaders between religious communities who carry out a common vision of realizing harmonious and harmonious daily lives of citizens. Religious leaders provide charisma, inspiration, intellectual stimulation, and individual consideration that are oriented towards inter-religious harmony by harmonizing religious values while applying the principles of leadership Rasulullahâ€™s style, so that they can manifest themselves as caliphs on earth, who are always committed to carrying out benefit.